“Desarrollo de un modelo de optimización para la expansión del sistema de transmisión considerando criterios de confiabilidad” - Yugcha Quinatoa, William Germánico (2022)
The In this research, the model of transmission lines planning is made according to the growth of the demand and the electric generation to supply electric energy to the whole population of the country. The problem is that the load centers, due to their geographical location, are far from the generation center and this allows us to build new transmission lines that allow transporting the energy generated to the load centers while complying with important requirements such as quality, reliability and safety, thus guaranteeing the adequate management of the electric resources.